Oral Diseases During Systemic Psoriatic Drugs: A Review of the Literature and Case Series - Annunziata Raimondo; Federica Di Spirito; Serena Lembo (Mattioli1885, 2024)
Introduction: the oral health in psoriatic patients seems to be compromised respect to control individuals: many published studies have investigated the relationship between psoriatic disease and gingivitis, periodontitis, and missing teeth. However, data from these studies are not yet consistent and exhaustive. Moreover, no studies have considered the possible specific effects of conventional and biological systemic psoriatic treatments. Object: we report a narrative review of the literature about the possible link between anti-psoriatic drugs and oral disease onset, and case series of patients that have experienced oral disease during systemic therapy for psoriasis. Methods: this is a narrative review. The literature search was performed using MEDLINE databases. From the selected articles, additional references were identified by a manual search among the cited literature. Results: Oral adverse events during psoriatic therapies can be found as sporadic cases. The specific mechanisms of interplay between oral anatomic structures and the pathway targeted by the systemic agents will be deeply investigated. Conclusion: It should be recommended to all psoriatic patients who are candidates for conventional or biological systemic therapy to examine their oral state by a dentist and dermatologist with regular follow-up, to prevent oral health complications. Dermatologists and oral medicine specialists should be ready to recognize and manage this increasing number of oral adverse drug reactions during systemic treatments for psoriatic disease, providing patients with sufficient information about this risk and stressing the fundamental importance of regular dental assessments, and good oral hygiene.